Analisis Pengelolaan Sumber Daya Manusia dalam Upaya Peningkatan Kualitas Kinerja Individu: Studi Kasus di Kantor PWI Sumut - Zainarti; Sitepu, Elfran Dinata; Tarigan, Dinda Pratiwi br; Putri, Siti Annisa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Currently, with the rise of the media, the flow of information received by the public is different, professional journalists are an important pillar in informing the public. As a basis for action and improving the quality of life, human resource development has many things needed because it has important aspects in increasing productivity (Effendi and Sulistyorini, 2021). The purpose of this research is to find out the implementation of management and development of human resource management in the North Sumatra PWI organization. The research conducted by this writer uses a qualitative approach where the data is obtained without using numbers. The researcher chose a qualitative approach because it felt clearer and broader in the discussion. The use of a qualitative approach is intended to obtain original and natural data. This means that data is in accordance with the real situation and has deep meaning. PWI Sumut has carried out well the development of its human resources and encouraged its members to behave professionally in carrying out the profession as journalists through the training provided. Starting from the development of knowledge and skills, deepening the code of ethics, and competency tests which become formal development in the journalist profession. Although there are still some members who violate the journalistic code of ethics. Keywords: human resources, improving the quality of performance, North Sumatra PWI office